In Defense of Soundiness: A Manifesto - Livshits, Benjamin; Sridharan, Manu; Smaragdakis, Yannis; Lhoták, Ondřej; Amaral, J. Nelson; Chang, Bor-Yuh Evan; Guyer, Samuel Z.; Khedker, Uday P.; Møller, Anders; Vardoulakis, Dimitrios (Communications of the ACM, 2015)
The article discusses soundness of static program analysis. The authors say soundness implies accounting for all possible executions of a program, the calculation of an over-approximation, and an avoidance of spurious results. In their view no whole-program analysis tool meets this standard, a fact that most members of the research community are unaware of. To address this situation they propose a type of analysis called soundy that is characterized by over-approximation for most features of a programming language, but under-approximation for a specific subset.